Asuransi Kecelakaan Kendaraan Bermotor Roda Dua Sebagai Moda Transportasi Umum Berbasis Online - Hezron Sabar Rotua Tinambunan; Bagas Waskito; Muhammad Bayu Rizhaldi; Athia Fadzri K.R. Uno (Fakultas Hukum Universitas Islam Indonesia, 2019)
This research focuses on two discussions, first, to analyze the arrangement of accident insurance for two-wheeled motor vehicles as a mode of online-based public transportation in Law No. 22 of 2009 on Traffic and Road Transportation (LLAJ Law). Second, to analyze the mechanism of insurance fulfillment for losses arising from the accidents of two-wheeled motor vehicle as an online-based public transportation mode. This research is a normative legal study. It concludes that first, PT. Jasa Raharja cannot provide protection for people who take the two-wheeled motor vehicles as a means of public transportation, because such vehicles are not included as the public motor vehicles according to the LLAJ Law. However, the providers of public transportation services with two-wheeled motor vehicles as the means of transportation can partner-up with the private insurance companies, or they can provide their own insurance system. Second, if the insurance is not provided, then public transportation service providers can be deemed as default based on the terms and conditions that have been made. Improvements to the LLAJ Law are necessary especially regarding the unclear provisions relating to the accountability of public transport companies and technology-based application provider companies.